A decision-support framework for suspension of public infrastructure projects: a combined use of neutrosophic AHP and TOPSIS - Okudan, Ozan; Demirdogen, Gokhan; Isik, Zeynep (EMERALD GROUP PUBLISHING LTD, 2025)
PurposeThe purpose of this study is to develop a decision-support framework that can be used by decision-makers to suspend public infrastructure projects. Additionally, the study also investigates how to select the most convenient infrastructure project for suspension.Design/methodology/approachThe proposed framework includes an extensive set of factors and a novel comparison mechanism that can reveal the most convenient infrastructure project to be suspended. A comprehensible literature review and focus group discussion (FGD) sessions were conducted to identify factors that should be considered for suspension. Then, the neutrosophic analytic hierarchy process (N-AHP) method was used to determine the relative importance of the factors. Finally, the proposed comparison mechanism was demonstrated through a hypothetical case study and Technique for order of preference by similarity to ideal solution (TOPSIS) analysis.FindingsResults showed that suspension decisions cannot be made merely based on financial factors. Instead, the other aspects, namely Technical and managerial and Social and Environmental, should also be taken into consideration. Second, factors related to the initial investment, cost of refinancing, cash flow, permits and approvals, insufficiency of bidders, degradation of the components, reputation, impact on stakeholders and criticality of the infrastructure were particularly elaborated as the most significant, needing the utmost attention of the decision-makers. Lastly, the results demonstrated that the proposed comparison mechanism has considerable potential to identify the most convenient infrastructure project for suspension.Originality/valuePublic infrastructure projects are often under pressure due to the inflationary state and economic stagnation of countries after major crises. The suspension decision for infrastructure projects necessitates comprehensible assessments to consider all consequences. Studies have widely investigated the contractual and legal aspects of project suspension in light of existing literature. However, little effort has been devoted to identifying the factors that decision-makers should consider before suspending a particular infrastructure project. Furthermore, existing literature does not investigate how to select the most convenient infrastructure project for suspension either. Thus, by developing a specific suspension framework for infrastructure projects by considering various factors, this study is the earliest attempt to examine the contract suspension mechanism of public infrastructure projects. In this respect, the study significantly contributes to the theory of contract management domain and has important managerial implications.
Keywords: Public infrastructure projects; Economic and political turmoils; Suspension of construction contracts; Neutrosophic AHP; TOPSIS; MCDM; FUZZY AHP; RISK-MANAGEMENT; FOCUS GROUP; MEGAPROJECTS; METHODOLOGY; STRATEGIES; SELECTION; DESIGN; MODELS; ENERGY; Engineering; Business & Economics